Randomised controlled double blind study of role of recombinant erythropoietin in the prevention of chronic lung disease. Issue 3 (1st May 1997) - Griffiths, Gill; Lall, Ranjit; Chatfield, Sue; Short, Andrew; Mackay, Peter; Williamson, Paula; Brown, Julia; Levene, Malcolm I
Abstract : AIM: To evaluate the role of recombinant human erythropoietin (R-HuEpo) in reducing iron infusion, which may exacerbate free radical damage, leading to chronic lung disease. METHODS: A multicentre, randomised, placebo controlled, double blind study was carried out in four neonatal intensive care units in Yorkshire. Infants were randomly allocated and received either R-HuEpo (480 U/kg/wk) or placebo by twice weekly subcutaneous injection. The primary outcome measure was the number of days on respiratory support and a secondary outcome the number of blood transfusions required. RESULTS: Forty two very low birthweight (VLBW) infants were randomly allocated. There was little difference in the need for respiratory support one month after randomisation, but subsequently there was a trend towards a reduction in the proportion requiring respiratory support in the R-HuEpo group (difference at three months −0.50, 95% confidence interval −1.00, 0.17). During stay in hospital, the median number of blood transfusions was lower for infants in the R-HuEpo group (difference in medians −2, 95% CI −4, 0). The study was stopped early because of failure to recruit babies at the expected rate. CONCLUSIONS: R-HuEpo seems to reduce the number of days in oxygen for ill VLBW infants. These data could be used to construct a larger multicentre study to evaluate this effect further.